Apolipoprotein B100/Low-Density Lipoprotein Regulates Proteolysis and Functions of von Willebrand Factor under Arterial Shear - Cao, Wenjing; Abdelgawwad, Mohammad S.; Li, Jingzhi; Zheng, X. Long (Thrombosis and Haemostasis, 2019)
Background Proteolytic cleavage of von Willebrand factor (VWF) by a plasma a disintegrin and metalloproteinase with a thrombospondin type 1 motifs, member 13 (ADAMTS13) is regulated by shear stress and binding of coagulation factor VIII, platelets or platelet glycoprotein 1b, and ristocetin to VWF.Objective Current study aims to identify novel VWF binding partners that may modulate VWF functions under physiological conditions.Methods A deoxyribonucleic acid aptamer-based affinity purification of VWF, followed by tandem mass spectrometry, functional, and binding assays was employed.Results Apolipoprotein B100/low-density lipoprotein (apoB100/LDL) was identified as a novel VWF-binding partner. Purified apoB100/LDL was able to accelerate the proteolytic cleavage of VWF by ADAMTS13 under shear in a concentration-dependent manner. This rate-enhancing activity was dramatically reduced when apoB100/LDL was oxidized. More interestingly, the oxidized apoB100/LDL appeared to compete with native apoB100/LDL for its enhancing activity on VWF proteolysis under shear. As a control, a purified apoA1/high-density lipoprotein (apoA1/HDL) or apoB48 exhibited a minimal or no activity enhancing VWF proteolysis by ADAMTS13 under the same conditions. Both VWF and ADAMTS13 were able to bind native or oxidized apoB100/LDL with high affinities. No binding interaction was detected between VWF (or ADAMTS13) and apoA1/HDL (or apoB48). Moreover, apoB100/LDL but not its oxidized products inhibited the adhesion of platelets to ultra large VWF released from endothelial cells under flow. Finally, significantly reduced ratios of high to low molecular weight of VWF multimers with increased levels of plasma VWF antigen were detected in LDLR−/− mice fed with high cholesterol diet.Conclusion These results indicate that apoB100/LDL may be a novel physiological regulator for ADAMTS13-VWF functions.
Keywords: apoB100; low-density lipoprotein; von Willebrand factor; ADAMTS13; thrombosis; endothelial cells